Foldable responsive surfaces: two design studios with a comprehensive workflow - Osório, F. C.; Paio, A.; Oliveira, S.; Casale, A.; Valenti, G.; Calvano, M. (eCAADe 2017 – ShoCK!, 2017)
The adopted methodology was defined by a multidisciplinary team with a strong believe in the efficiency of learning-by-doing design studios which resulted in an experimental digital workflow to create responsive surfaces based on the geometry of Rigid Origami. The workflow comprehends all the matters related to the creation of such surfaces, from the conception and definition of the surface's design using Rigid Origami's geometry, passing through the virtual simulation of the movement, digital fabrication and material's choice, then the mechanics behind the movement, interaction programming, and the assembly of it all in real scale prototypes.